Comparison of changes FEV1 in Bronchodilator and Corticosteroid Combinations for Patients Chronic Obstructive Pulmonary Disease Stable in Balai Besar Kesehatan Paru Masyarakat (BBKPM) Hospital Surakarta - Fajar Amirulah Apoteker (Jurnal Inovasi Farmasi Indonesia (JAFI), 2020)
The objective of the present study is to study the relationship for use bronchodilator combined to corticosteroids between Dyspnoea BORG Scale, respiratory rate (rr) and Forced Expiratory Volume in first second (FEV1) in COPD patients. This Prospective observational study was conducted on 57 patient during November 2018 and April 2019 at Balai Besar Kesehatan Paru Masyarakat Hospital, Surakarta. The characteristic patient COPD include gender, age, smoker or non-smoker, worker or non-worker correlated not significanly with use bronchodilator combined to corticosteroids  (p>0,05). % FEV1 and respiratory rate (rr) not significanly for COPD patients with use bronchodilator combined to corticosteroid  (p>0,05). Dyspnoea BORG Scale correlated significanly for COPD patients with use bronchodilator combined to corticosteroid  (p<0,05). We conclude that in COPD patients, the combined use of bronchodilator with corticosteroids is more effective in reducing the dyspnoea than bronchodilator alone.